A Comparative Analysis of Methods (LC-MS/MS, LC-MS and Rapid Test Kits) for the Determination of Diarrhetic Shellfish Toxins in Oysters, Mussels and Pipis - Penelope A. Ajani; Chowdhury Sarowar; Alison Turnbull; Hazel Farrell; Anthony Zammit; Stuart Helleren; Gustaaf Hallegraeff; Shauna A. Murray (Toxins, 2021)
Rapid methods for the detection of biotoxins in shellfish can assist the seafood industry and safeguard public health. Diarrhetic Shellfish Toxins (DSTs) are produced by species of the dinoflagellate genus Dinophysis, yet the comparative efficacy of their detection methods has not been systematically determined. Here, we examined DSTs in spiked and naturally contaminated shellfish–Sydney Rock Oysters (Saccostrea glomerata), Pacific Oysters (Magallana gigas/Crassostrea gigas), Blue Mussels (Mytilus galloprovincialis) and Pipis (Plebidonax deltoides/Donax deltoides), using LC-MS/MS and LC-MS in 4 laboratories, and 5 rapid test kits (quantitative Enzyme-Linked Immunosorbent Assay (ELISA) and Protein Phosphatase Inhibition Assay (PP2A), and qualitative Lateral Flow Assay (LFA)). We found all toxins in all species could be recovered by all laboratories using LC-MS/MS (Liquid Chromatography—tandem Mass Spectrometry) and LC-MS (Liquid Chromatography—Mass Spectrometry); however, DST recovery at low and mid-level concentrations (<0.1 mg/kg) was variable (0–150%), while recovery at high-level concentrations (>0.86 mg/kg) was higher (60–262%). While no clear differences were observed between shellfish, all kits delivered an unacceptably high level (25–100%) of falsely compliant results for spiked samples. The LFA and the PP2A kits performed satisfactorily for naturally contaminated pipis (0%, 5% falsely compliant, respectively). There were correlations between spiked DSTs and quantitative methods was highest for LC-MS (r2 = 0.86) and the PP2A kit (r2 = 0.72). Overall, our results do not support the use of any DST rapid test kit as a stand-alone quality assurance measure at this time.